2000
DOI: 10.1111/j.1439-0450.2000.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and Immunohistochemical Study of Lambs Experimentally Infected with Fasciola hepatica and Schistosoma bovis

Abstract: Summary The aim of this study was to investigate the cross‐resistance between Fasciola hepatica and Schistosoma bovis in lambs assessing parasitologic, gross pathologic, histopathologic and immunohistochemical changes in liver and small intestine. Thirty Castellana breed lambs were divided into five comparable groups and exposed to F. hepatica/S. bovis (group F/S), S. bovis/F. hepatica (group S/F), S. bovis (group S) or F. hepatica (group F) and six unexposed lambs were used as non‐infected controls (group C).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Since both trematodes cause significant liver pathology (Ferreras et al, 2000;Phiri et al, 2006b), when one infection is established, it may exclude the other from establishing. Since both trematodes cause significant liver pathology (Ferreras et al, 2000;Phiri et al, 2006b), when one infection is established, it may exclude the other from establishing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since both trematodes cause significant liver pathology (Ferreras et al, 2000;Phiri et al, 2006b), when one infection is established, it may exclude the other from establishing. Since both trematodes cause significant liver pathology (Ferreras et al, 2000;Phiri et al, 2006b), when one infection is established, it may exclude the other from establishing.…”
Section: Discussionmentioning
confidence: 99%
“…Since both trematodes cause significant liver pathology (Ferreras et al, 2000;Phiri et al, 2006b), when one infection is established, it may exclude the other from establishing. In experimental studies, primary infection with Schistosoma or Fasciola species in ruminants has been reported to result in enhanced resistance to heterologous challenge (Bushara et al, 1978;Sirag et al, 1981;Yagi et al, 1986;Ferreras et al, 2000;Almeida et al, 2003). Although the correlation coefficient between the two trematodes in our study was negative, the relationship was not significant (P ¼ 0.390).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been shown that M2 macrophages isolated from mice during infection with F. hepatica promote the polarization of Th2 cells (69,70). Thirdly, there is a significant increase in the number of mast cells observed at the site of infection and in the gut mucosa (73)(74)(75)(76)(77). While mast cells are critical to the expulsion of gut helminths (78), their role in Fasciola infection is not clear, although we hypothesize that given that mast cells have an important role in wound healing and tissue remodelling (79), they are recruited to combat the extensive tissue damage caused by migratory flukes (80).…”
Section: Immune Responses and Immunity To Liver Flukementioning
confidence: 99%
“…Similarly, mast cells are observed in the chronic stages of Schistosoma infection, when T H 2/T reg immune responses are predominant , again implicating an important role for mast cells in shaping the adaptive immune response. Increased mast cell infiltration in the liver remains a key feature of Fasciola hepatica infection , and in rodent models, this is dominated by T H 2/T reg responses within hours of infection.…”
Section: The Role Of Mast Cells In Helminth Infectionmentioning
confidence: 99%